2016
DOI: 10.1016/j.ensci.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography scanning and stroke mortality in an urban medical unit in Cameroon

Abstract: BackgroundDespite the increasing availability of head computerized tomography (CT) in resource-limited settings, it is unclear if brain-imaging-based diagnosis of stroke affects the outcomes in the absence of dedicated structures for acute stroke management.ObjectivesIn a major referral hospital in the capital city of Cameroon, we compared in-hospital mortality rates in patients with a WHO-based diagnosis of stroke between participants with and without brain imaging on admission.MethodsStroke patients with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Accordingly, the pooled in-hospital mortality was found to be 16% (14%-19%). The frequency of in-hospital mortality was reported among different countries such Iran 20.52% [34] Sweden(15.47%) [19] and Cameroon 20.62% [30]. Even though hospital admission facilitates the recovery of stoke patients, in the meantime, it predisposes patients for hospital acquired infections which complicate the survival of stroke patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the pooled in-hospital mortality was found to be 16% (14%-19%). The frequency of in-hospital mortality was reported among different countries such Iran 20.52% [34] Sweden(15.47%) [19] and Cameroon 20.62% [30]. Even though hospital admission facilitates the recovery of stoke patients, in the meantime, it predisposes patients for hospital acquired infections which complicate the survival of stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty two studies assessed overall mortality due to stroke. Twelve studies were from Africa [7][8][17][18][19][20][21][22][23][24][25][26], six from Europe [27][28][29][30][31][32], six from Asia [33][34][35][36][37][38], five from North America [39][40][41][42][43] and two from Latin America [44][45].Seventeen studies reported 30-day mortality rate of stroke whereas twenty two studies measured in-hospital mortality. Detailed explanations on study characteristics are shown in the supplementary table (table 1).…”
Section: Study Characteristics and The Selection Processmentioning
confidence: 99%
“…We are not aware of a previous study that looked specifically at the association between time to perform brain CT on admission and in-hospital mortality for stroke in sub-Saharan Africa. Lekoubou et al in Cameroon had found that no CT performed on admission was predictor of mortality for ischemic or hemorrhagic stroke patients [29]. According to recommendations, a suspected stroke patient should have a CT within 3 hours of symptom onset to allow for appropriate intervention to arrest progression of neurological deficits [30].…”
Section: Mortality Risk Factorsmentioning
confidence: 99%
“…According to a survey of stroke experts, the minimum investigations required for stroke unit care were brain CT (prioritized for stroke patients), carotid Doppler, and ECG [ 38 ]. A previous study of stroke patients in a Cameroonian medical unit confirmed the importance of brain CT in mortality reduction in a resource-constrained setting [ 39 ]. Recent studies have suggested an increase in the prevalence of extracranial carotid atherosclerosis in Africans [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 79%